Step into Loyalty: Uncovering What Drives Sneaker Satisfaction and Brand Devotion among Millennials - Ndlela, Thubelihle; Kambule, Nomathamsanqa Khanyisile; Chiliya, Norman (International Review of Management and Marketing, 2025)
The aim of the study was to investigate factors that determine brand loyalty towards certain sneaker brands amongst millennials in South Africa. Through an online survey, data was obtained over a 2-month period from 333 young consumers residing in Braamfontein, a popular shopping district in Johannesburg South Africa selected through non-probability sampling. Analysis of data was conducted in SPSS and AMOS software in order to generate descriptive statistics and hypotheses testing respectively. The findings from this study highlight the powerful influence of perceived quality and aesthetics on brand satisfaction, particularly among South African millennials. Notably, brand satisfaction emerged as the key driver of brand loyalty in this demographic. For sneaker marketers, this underscores the need to prioritize brand loyalty strategies when engaging millennial consumers in South Africa’s dynamic apparel market. Through developing and testing a theoretical framework, this research sheds light on the crucial factors that cultivate brand loyalty towards sneakers, bridging an important gap in understanding how millennials in emerging markets connect with sneaker brands. These insights offer valuable guidance for marketers seeking to capture and sustain millennial loyalty in this competitive space.